2008
DOI: 10.2169/internalmedicine.47.0334
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Associated with Autoimmune Pancreatitis in Remission

Abstract: In January 2007, an 80-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 22 publications
3
44
2
Order By: Relevance
“…Twelve cases of pancreatic cancer complicated with AIP have been previously reported [17][18][19][20][21] Among the 12 cases, 5 occurred concurrently with AIP, and 7 occurred from 3 to 5 years after the diagnosis of AIP. It has been estimated that, generally, two thirds of pancreatic cancers occur in the head region.…”
Section: Aip and Malignanciesmentioning
confidence: 99%
“…Twelve cases of pancreatic cancer complicated with AIP have been previously reported [17][18][19][20][21] Among the 12 cases, 5 occurred concurrently with AIP, and 7 occurred from 3 to 5 years after the diagnosis of AIP. It has been estimated that, generally, two thirds of pancreatic cancers occur in the head region.…”
Section: Aip and Malignanciesmentioning
confidence: 99%
“…Recently, there have been reports in the literature of pancreatic cancer complicating AIP years after its diagnosis. [35][36][37] It is unclear if subsequent development of pancreatic cancer represents a true complication of longstanding AIP or a chance occurrencein an elderly man who also happened to have AIP. 35 Long-term studies in large cohorts of AIP are needed to determine if AIP predisposes to subsequent development of pancreatic cancer because cancer typically occurs decades after onset of chronic pancreatitis.…”
Section: Follow-upmentioning
confidence: 99%
“…Recently some researches showed that patients with IgG4-RD were at the risk of malignant tumors [10,11] or hematological malignancies such as lymphoma [12,13]. IgG4-RD can happen before or after the diagnosis of lymphoma.…”
Section: Discussionmentioning
confidence: 99%